Tinjauan Hukum Pengunaan Aplikasi inDriver MOD Menurut Fatwa MUI Nomor 1/MUNAS VII/MUI/5/2005 Tentang Hak Kekayaan Intelektual - Fahri, Sutan; Khalid, Khalid (UNES Law Review, 2023)
Several large companies are racing to establish app-based transportation companies, and one of them is inDriver. The inDriver app, particularly for drivers, is not immune to application modifications. One of the widely circulated modified applications among drivers is the inDriver MOD Autobid. Given the high interest and usage of inDriver by the public for their daily needs, it's undeniable that the number of inDriver drivers has significantly increased, intensifying the competition among them for orders.Despite this, the inDriver order system is still the one assigning orders to drivers, rather than a "first come, first served" basis. However, in the inDriver driver application, every incoming order must be manually accepted within a certain time frame. If there is no response from the driver within that period, the system will reassign the order to another driver. To minimize the occurrence of failed order acceptances, there is now the inDriver mod Autobid. inDriver Mod is a modified version of the inDriver driver application, with changes made to the system files to enable the automatic functioning of the autobid feature when the application is opened/activated.This modification allows drivers to avoid installing an autoclick application to activate the autobid feature, similar to autobid features in platforms like Lalamove or other online motorcycle taxi applications. Consequently, every time an order comes in, it is automatically accepted. The use of modified applications, especially among online motorcycle taxi drivers, particularly focuses on one online motorcycle taxi application— inDriver. Those involved, both the modifiers and users of the modified application, are found to be in violation of Article 9 paragraph 3 of the Copyright Law, which states, "Any person without the permission of the Creator or Copyright Holder is prohibited from duplicating and/or commercially using the Creation."In Islam, attention is also given to copyright, as it is seen as a form of protection of rights between individuals to achieve harmony in the rights of each person. The National Sharia Council (DSN) through the Decree of DSN Ulama Council has also issued a fatwa on the protection of Intellectual Property Rights outlined in the FATWA of the Indonesian Ulama Council Number: 1/MUNAS VII/MUI/5/2005, which states that selling and pirating others' intellectual property without legal rights is prohibited.